(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
Diagnostic analysis feels urgent when it comes to set apart different types of Parametricism. These dualities come in many forms: semantic terminology; the discerning between a style and a set of digital tools; the enthusiasts and their audiences; the democracy of the tools and many others. This paper goes through a brief historical background raising questions based on the fast growing writings that try to fill in the deficiency on the theoretical field that the emergent style faces. Aiming to discuss if Parametricism is ready or not to be asserted as the great new style of the generation we find that, ironically, many parameters appear in this input.